Growth kinetics and biodeterioration of polypropylene microplastics by Bacillus sp. and Rhodococcus sp. isolated from mangrove sediment - Auta, Helen Shnada; Emenike, Chijioke Uche; Jayanthi, B.; Fauziah, Shahul Hamid (Elsevier, 2018)
Interest in the biodegradation of microplastics is due to their ubiquitous distribution, availability, high persistence in the environment and deleterious impact on marine biota. The present study evaluates the growth response and mechanism of polypropylene (PP) degradation by Bacillus sp. strain 27 and Rhodococcus sp. strain 36 isolated from mangrove sediments upon exposure to PP microplastics. Both bacteria strains were able to utilise PP microplastic for growth as confirmed by the reduction of the polymer mass. The weight loss was 6.4% by Rhodococcus sp. strain 36 and 4.0% by Bacillus sp. strain 27 after 40 days of incubation. PP biodegradation was further confirmed using Fourier-transform infrared spectroscopy and scanning electron microscopy analyses, which revealed structural and morphological changes in the PP microplastics with microbial treatment. These analyses showed that the isolates can colonise, modify and utilise PP microplastics as carbon source.